Effect and potential mechanism of oncometabolite succinate promotes distant metastasis of colorectal cancer by activating STAT3 - Jiangnan Yu; Hong Yang; Lin Zhang; Suye Ran; Qing Shi; Pailan Peng; Qi Liu; Lingyu Song (BMC Gastroenterology)
Abstract To investigate the effect of Oncometabolite succinate on colorectal cancer migration and invasion and to initially explore the underlying mechanism.Succinate acid detection kit detected the succinate content in tissues. The growth of colorectal cancer cells was measured by cck-8 assay, wound-healing migration assay and transwell migration and invasion assays, and then explored the level of epithelial-mesenchymal transition (EMT) and STAT3/ p-STAT3 expression by western blot analysis and quantitative real-time PCR for mRNA expression. We found that succinate levels were significantly higher in carcinoma tissues than paracancerous tissues. After succinate treatment, the colorectal cancer cell lines SW480 and HCT116 had enhanced migration and invasion, the expression of biomarkers of EMT was promoted, and significantly increased phosphorylation of STAT3. In vivo experiments also showed that succinate can increase p-STAT3 expression, promote the EMT process, and promote the distant metastasis of colorectal cancer in mice.Succinate promotes EMT through the activation of the transcription factor STAT3, thus promoting the migration and invasion of colorectal cancer.